Loneliness as a gender-specific predictor of physical and mental health-related quality of life in older adults - Böhlen, Friederike; Maatouk, Imad; Friederich, Hans-Christoph; Schöttker, Ben; Brenner, Hermann; Wild, Beate (Quality of life research, 2022)
Purpose  Health-related quality of life (HRQOL) in older persons is influenced by physical and mental health, as well as by their social contacts and social support. Older women and men have disparate types of social networks; they each value social ties differently and experience loneliness in unique and personal ways. The aim of this study is, therefore, to determine the longitudinal association between loneliness and social isolation with HRQOL in older people—separated by gender. - Methods  Data stem from the third and fourth follow-up of the ESTHER study—a population-based cohort study of the older population in Germany. A sample of 2171 older women and men (mean age: 69.3 years, range 57-84 years) were included in this study; HRQOL was assessed by using the Short Form-12 questionnaire (SF-12). Data on physical and mental health, loneliness, and social networks were examined in the course of comprehensive home visits by trained study doctors. Gender-specific linear regression analyses were performed to predict physical quality of life (measured by the PCS, physical component score of the SF-12) and mental quality of life (measured by the MCS, mental component score) after three years, adjusted by socioeconomic variables as well as physical, mental, and social well-being. - Results  At baseline, PCS was 41.3 (SD: 10.0) in women and 42.2 (SD: 9.6) in men (p = .04). MCS was 47.0 (SD: 10.2) in women and 49.6 (SD: 8.6) in men (p < .001). In both genders, PCS and MCS were lower three years later. Loneliness at t0 was negatively associated with both PCS and MCS after three years (t1) among women, and with MCS but not PCS after three years among men. In both genders, the strongest predictor of PCS after three years was PCS at t0 (p < .001), while the strongest predictors of MCS after three years were MCS and PCS at t0. - Conclusion  HRQOL in elderly women and men is predicted by different biopsychosocial factors. Loneliness predicts decreased MCS after three years in both genders, but decreased PCS after three years only in women. Thus, a greater impact of loneliness on the health of older women can be surmised and should therefore be considered in the context of their medical care.
Online veröffentlicht: 2 Dezember 2021
Gesehen am 03.07.2023